Studying in Turkey: Perceptions of international social studies teacher candidates - YILMAZ, KAYA; İBRAHİMOĞLU, ZAFER (My University, 2018)
The primary aim of this study was to reveal how international social studies teacher candidates perceive/make sense of their experiences in Turkey. The participants were three international social studies teacher candidates studying at an Istanbul university. The data were gathered from semi-structured interviews, with the analysis following content analysis steps. It was found that the international social studies teacher candidates had negative views of Turkey before coming to the country; however, there were positive changes in their perceptions during their time in Turkey, with all believing that they would have gained a great deal by the time they return to their countries. The main achievements that participants believe to earn by studying in Turkey are a qualified/democratic education and citizenship awareness as a reflection of this education. Keywords: International students, social studies, studying in Turkey, teacher candidates
Studying in Turkey